2008
DOI: 10.1093/humrep/den192
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and chemokines in follicular fluids and potential of the corresponding embryo: the role of granulocyte colony-stimulating factor

Abstract: Individual FF composition is related to the development of the corresponding in vitro generated embryo and its potential of implantation. Individual FF G-CSF may provide a non-invasive biomarker of implantation that needs to be evaluated together with in vitro observation to select the oocyte, and hence the embryo, to transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 49 publications
8
66
2
1
Order By: Relevance
“…A positive association of IL-6 with oocyte maturation [31] and IL-1β with embryo development and pregnancy [32] is documented. A majority of findings have indicated that IL-12 is negatively associated with folliculogenesis, oocyte quality, and implantation [30,33,34]. TNF-α, reported to be significantly higher in follicular fluids corresponding to poor-quality oocytes and embryos, possibly deteriorates the microenvironment in the follicle [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…A positive association of IL-6 with oocyte maturation [31] and IL-1β with embryo development and pregnancy [32] is documented. A majority of findings have indicated that IL-12 is negatively associated with folliculogenesis, oocyte quality, and implantation [30,33,34]. TNF-α, reported to be significantly higher in follicular fluids corresponding to poor-quality oocytes and embryos, possibly deteriorates the microenvironment in the follicle [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative determination of cytokines was performed with a bead-based multiplex immunoassay, as previously described (Lédée et al 2008). Briefly a bead-based multiplex immunoassay (Bio-Rad) and a Bioplex 200 system (Bio-Rad; Luminex Map Technology) were used to measure simultaneously in cell culture supernatants the concentrations of the following cytokines and chemokines: IL1b, IL1Ra, IL2, IL4, IL5, IL6, IL8, IL9, IL10, IL12, IL13, IL15, IL17A, IFN-g, TNFa, G-CSF, GM-CSF, VEGF, PDGF, basic fibroblast growth factor (bFGF) interferon g/inducible protein-10 (IP-10), monocyte chemotactic protein-1 (MCP-1), RANTES, eotaxin, macrophage inflammatory protein-1a (MIP-1a), and MIP-1b.…”
Section: Determination Of Cytokine and Chemokine Concentrationsmentioning
confidence: 99%
“…Many couples still remain unsuccessful after several IVF attempts causing deep effect on quality of life and a heavy financial burden (Zeyneloglu & Onalan 2014). With the recent advances in understanding the important role of granulocyte colony-stimulating factor (GCSF) in reproduction, and the detection of GCSF receptors in placental cytotrophoblasts, syncytiotrophoblasts, decidual stromal cells, endometrial gland cells, and follicular cells (Saito et al 1994, Miyama et al 1998, McCracken et al 1999, Salmassi et al 2005, Ledee et al 2008, Rahmati et al 2014, GCSF started to attract attentions in gynecology, especially in patients with recurrent abortions and/or infertility.…”
Section: Introductionmentioning
confidence: 99%